High Resistance of Vector of West Nile Virus, Culex pipiens Linnaeus (Diptera: Culicidae) to Different Insecticides Recommended by WHO in Northern Iran - Ghorbani, Fatemeh (J Arthropod Borne Dis, 2018)
BACKGROUND: Culex pipiens is a mosquito species distributed in different parts of Iran. It is known as vector of some diseases as well as a nuisance insect. A successful control campaign needs to study the biology, ecology and susceptibility status of the target pest. The aim of this study was to investigate the susceptibility status of Culex pipiens to some insecticides recommended by WHO in north of Iran. METHODS: Larvae were collected from different breeding places in Sari County by standard dipping method. They were reared to adult stage in an under standard condition. World Health Organization (WHO) standard test kits and the diagnostic dose of 12 imagicides were used for adults, while two larvicides were used against larvae. RESULTS: The least and highest mortality rates after exposure to insecticides were 4.7% (Propoxur 0.1%) and 76.4% (Etofenprox 0.5%), respectively. Larvae showed high resistance to temephos (19.19%) and malathion (54.63%). Culex pipiens was found to be resistant to all used insecticides/larvicides at diagnostic dose. CONCLUSION: Intensive use of pesticides against agriculture and urban pests increased the resistance level of this species to different insecticides, although currently there is no control program against it. Study on the mechanisms of resistant in this species to different insecticides is recommended.